Isolation and Molecular Characterization of Methicillinresistant Staphylococcus aureus (MRSA) from Swine following Spa Typing - Ganesan, Indhuja; Antony, Prabhaker X.; Vasu, Jayalakshmi; Srinivas, Mouttou V.; Mukhopadhyay, Hirak K.; Thanislass, Jacob (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The objective of this study was to isolate the Methicillin-resistant Staphylococcus aureus (MRSA) from the nasal swabs of swine andfurther characterize the isolates by spa typing. 116 (91.34%) Staphylococcal isolates were obtained from 127 nasal swabs of swinefrom organized and unorganized pig farms in and around the Puducherry region (India). The nuc gene specific for S. aureus wasfound in 97 (83.62%) isolates from swine. Methicillin resistant gene mecA was detected in 23 isolates (19.83%), and none of thestaphylococcal isolates from swine carried the mecC gene. Ten representatives MRSA isolates from swine were subjected to furthercharacterization using spa typing (Staphylococcus aureus protein A typing). Four different spa types were identified namely t657(40.0%, 4/10), t5983 (40.0%, 4/10), t005 (10.0%, 1/10) and t127 (10.0%, 1/10) from Puducherry region.
Keywords: Methicillin-resistance; mecA; Public health, Spa typing; Swine